Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/ki.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

What is nephrocalcinosis?

Abstract: The available publications on nephrocalcinosis are wide-ranging and have documented multiple causes and associations of macroscopic or radiological nephrocalcinosis, most often located in the renal medulla, with various metabolic and genetic disorders; in fact, so many and various are these that it is difficult to define a common underlying mechanism. We have reviewed nephrocalcinosis in relation to its definition, genetic associations, animal models, and putative mechanisms. We have concluded, and hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 73 publications
4
65
1
7
Order By: Relevance
“…While other experimental models have clearly demonstrated OPN’s anti-calcific property, our findings are unique in that they establish OPN as a simultaneous protector of both vascular and renal calcification. This is particularly noteworthy as clinical studies show a strong correlation between kidney stone formation and VC, and pathogenic links between nephrocalcinosis and VC have been hypothesized 1, 36 . Also, previous in vivo calcification models utilizing OPN KO animals have induced calcification in various ways such as graft implantation or oxalate administration (given orally or via injection) 3739 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While other experimental models have clearly demonstrated OPN’s anti-calcific property, our findings are unique in that they establish OPN as a simultaneous protector of both vascular and renal calcification. This is particularly noteworthy as clinical studies show a strong correlation between kidney stone formation and VC, and pathogenic links between nephrocalcinosis and VC have been hypothesized 1, 36 . Also, previous in vivo calcification models utilizing OPN KO animals have induced calcification in various ways such as graft implantation or oxalate administration (given orally or via injection) 3739 .…”
Section: Discussionmentioning
confidence: 96%
“…This accumulation of calcium in the kidney is due to increased urinary excretion of calcium, phosphorus, and/or oxalate in combination with a loss of protective urinary inhibitors of mineralization. There are many underlying diseases that cause nephrocalcinosis and depending on the etiology, nephrocalcinosis can cause progressive renal dysfunction and end stage renal disease (ESRD) 1 . Similar to nephrocalcinosis, vascular calcification (VC) is caused by an imbalance in pro-calcific and anti-calcific factors.…”
Section: Introductionmentioning
confidence: 99%
“…The RCALC1 phenotype has similarities to human NC, which includes the interstitial deposition of calcium phosphate in the renal papillae . For example, high‐resolution Fourier transform infrared microspectroscopy and electron diffraction studies have revealed that calcium phosphate crystals are the major component of Randall's plaque, which are the areas of the renal papillae that contain interstitial calcium phosphate deposits that provide a nidus of urothelial surface for calcium oxalate deposition .…”
Section: Resultsmentioning
confidence: 99%
“…Renal calcification may occur in the kidney parenchyma (nephrocalcinosis [NC]) or the collecting system (nephrolithiasis [NL], ie, kidney stones) . NL and NC affect ∼10% of the adult Western population by the age of 70 years, although such distinctions may be difficult in patients who may develop both NL and NC, and it has been reported that >50% to 70% of patients with kidney stones will have NC .…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen in a variety of congenital and acquired diseases. 1 Diagnosis is often made incidentally by imaging such as plain abdominal radiography, kidney ultrasonography and abdominal computed tomography. 2 In general, nephrocalcinosis is recognized as systemic disease and appropriate evaluation is needed to clarify underlying disease.…”
Section: Clinical Descriptionmentioning
confidence: 99%